Topical problems of theoretical psychology - Bagdonas, A. (Psichologija, 1989)
A critical review of different aspects of constructing the general theory of psychology and theoretical psychology as a highest level of its development is presented in the paper. The contemporary psychology is viewed as a disintegrated preparadigmatic science, the further progress of which is unthinkable without the synthesis of different schools, theories and levels (empirical, theoretical and practical). The causes of psychology disintegration are analysed; pretensions of cognitive psychology and other modern schools (humanistic psychology, transpersonalism) are criticized. Reductionist theories are not able to substitute for the general psychological theory. The development of psychology is shown as a cumulative process, which now and then is disturbed by microrevolutions caused by behaviourism, psychoanalysis and other schools. An example of such a microrevolution was the remaking of Soviet Marxist psychology initiated by L. Vygotsky. The integration of psychological knowledge and the construction of the general psychological theory may be fulfilled by using the multiple analysis of intertheoretical relations, the cooperation of psychologists from different countries, branches and schools of psychology, the extension of theoretical investigations in the field of psychology, axiomatisation and formalisation of its laws, regularities and principles.